The Factors that Influence People's Consumption of Moringa in Surabaya City - Desy Fajariyah; Pismia Sylvi (Jurnal Matematika Sains dan Teknologi, 2025)
The decrease in the prevalence of nutrition recorded in the Indonesian Nutrition Status Survey (SSGI) in 2021-2022 by 2.8% (Ministry of Health of Indonesia, 2023) indicates an improvement in the nutritional status of the community. One of the factors that influence nutritional status is the consumption pattern of nutritious vegetables. Moringa (Moringa Oleifera), has an important role in improving nutrition due to its high nutritional content. However, the utilisation of Moringa leaves is still limited due to the community's lack of understanding about the benefits and consumption of Moringa leaves. This study aims to identify the factors that influence people's consumption of moringa leaves with a case study in Surabaya City. A total of 70 respondents who had consumed moringa were selected through a two-stage cluster sampling method. Analyses were conducted to evaluate the influence of consumption goal variables, availability, price, and information sources on moringa consumption patterns. The results show that the source of information is a factor that has a significant effect on consumption patterns. These findings indicate the importance of disseminating appropriate information to increase the utilization of moringa in the moringa vegetable diet for people in Surabaya.